2013
DOI: 10.1186/1471-2202-14-74
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-fast speech comprehension in blind subjects engages primary visual cortex, fusiform gyrus, and pulvinar – a functional magnetic resonance imaging (fMRI) study

Abstract: BackgroundIndividuals suffering from vision loss of a peripheral origin may learn to understand spoken language at a rate of up to about 22 syllables (syl) per second - exceeding by far the maximum performance level of normal-sighted listeners (ca. 8 syl/s). To further elucidate the brain mechanisms underlying this extraordinary skill, functional magnetic resonance imaging (fMRI) was performed in blind subjects of varying ultra-fast speech comprehension capabilities and sighted individuals while listening to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
86
3
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(102 citation statements)
references
References 72 publications
9
86
3
4
Order By: Relevance
“…Nonetheless, both studies focused on cross-modal plasticity mechanisms and not in characterizing simultaneously the structure and function of visual cortical regions in the context of specific changes triggered by a retinal disorder. Additionally, the majority of reports on structural changes combine several ophthalmological conditions involving distinct mechanisms, which may hinder the understanding of specific brain changes triggered by a particular disease (Anurova et al, 2014, Boldt et al, 2014, Dietrich et al, 2013, Erika et al, 2014, Lee et al, 2014, Lewald and Getzmann, 2013, Park et al, 2009, Plank et al, 2011, Renier et al, 2013, Wang et al, 2014, Weaver et al, 2013, Xie et al, 2012). Previous studies with advanced stage patients with glaucoma and macular degeneration (Bogorodzki et al, 2014, Boucard et al, 2009, Chen et al, 2013, Hernowo et al, 2014, Plank et al, 2011, Yu et al, 2014, Zikou et al, 2012) and blind participants (Anurova et al, 2014, Jiang et al, 2009, Pan et al, 2007, Park et al, 2009, Ptito et al, 2008) reported reduced gray matter volume in the occipital cortex.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, both studies focused on cross-modal plasticity mechanisms and not in characterizing simultaneously the structure and function of visual cortical regions in the context of specific changes triggered by a retinal disorder. Additionally, the majority of reports on structural changes combine several ophthalmological conditions involving distinct mechanisms, which may hinder the understanding of specific brain changes triggered by a particular disease (Anurova et al, 2014, Boldt et al, 2014, Dietrich et al, 2013, Erika et al, 2014, Lee et al, 2014, Lewald and Getzmann, 2013, Park et al, 2009, Plank et al, 2011, Renier et al, 2013, Wang et al, 2014, Weaver et al, 2013, Xie et al, 2012). Previous studies with advanced stage patients with glaucoma and macular degeneration (Bogorodzki et al, 2014, Boucard et al, 2009, Chen et al, 2013, Hernowo et al, 2014, Plank et al, 2011, Yu et al, 2014, Zikou et al, 2012) and blind participants (Anurova et al, 2014, Jiang et al, 2009, Pan et al, 2007, Park et al, 2009, Ptito et al, 2008) reported reduced gray matter volume in the occipital cortex.…”
Section: Introductionmentioning
confidence: 99%
“…This exceptional skill allows for the processing of large amounts of written materials using screen-reading text-to-speech devices and may help, e.g., to better cope with the demands of college or university education. As a first approach to the elucidation of the cerebral mechanisms underlying these intriguing perceptual/cognitive capacities, a previous fMRI study of our group (Dietrich et al, 2013) delineated the hemodynamic activation pattern of late-blind and sighted individuals while listening to sentence utterances of a moderately fast (8 syl/s) or ultra-fast (16 syl/s) syllable rate. The proficiency of the blind subjects extended from low to high comprehension capabilities (up to >90%—in terms of the percentage of syllables in correctly reproduced words in a sentence repetition task) at 16 syl/s, whereas the performance level of sighted subjects fell consistently below 20%.…”
Section: Introductionmentioning
confidence: 99%
“…The proficiency of the blind subjects extended from low to high comprehension capabilities (up to >90%—in terms of the percentage of syllables in correctly reproduced words in a sentence repetition task) at 16 syl/s, whereas the performance level of sighted subjects fell consistently below 20%. Besides the classical perisylvian “language zones” of the left hemisphere [inferior frontal gyrus (IFG)/superior temporal cortex] and the supplementary motor area (SMA), blind people highly skilled in ultra-fast speech perception showed significant hemodynamic activation of right-hemispheric primary visual cortex (V1), contralateral fusiform gyrus (FG), and bilateral pulvinar (Pv) (Dietrich et al, 2013). In a recent Hypothesis and Theory paper (Hertrich et al, 2013b), an expanded model of speech perception was introduced to describe how blind subjects might use their visual system for ultra-fast speech perception.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, early onset blind individuals display activation of visual areas, including the primary visual cortex (V1), when reading braille [6,7] or comprehending ultra fast speech [8,9]. Also, in deaf individuals visual stimuli have been shown to activate auditory cortical areas, including the primary auditory cortex (A1) [10].…”
mentioning
confidence: 99%